(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Today, environmentally friendly solvent systems and eco-friendly reducing and capping agents have been used to create "Green" nanoparticles. The goal of the current work was to examine the manufacture of zinc oxid nanoparticles using pomegranate fruit extract as a reducing agent. In UV-vis spectra, the distinctive surface plasmon absorption peak of zinc at 370 nm served as proof that nanoscale zinc had formed. Scanning electron microscopy (SEM), energy dispersive X-ray analysis (EDAX), X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy were used to analyze the morphology and crystalline nature of the produced zinc molecule. Study the chemical composition of the peel extract by GC-MS chromatogram (Phytochemical analysis). Twenty-one significant peaks and the components matching to the peaks were found in the Punica granatum peel ethanolic extract used in the current study's chemical composition GC-MS chromatogram (Phytochemical) analysis. The current findings suggest that Punica granatum includes a number of bioactive ingredients.